Assessment of Nepalese prosthodontist’s attitude towards morphological completeness of dental arches in partially dentate older patients - Poudel, Sabina; Shrestha, Prabhat; Acharya, Lochana; Poudyal, Sijan (Journal of Chitwan Medical College, 2020)
Background: Complete dentition is not always appropriate for old aged medically compromised and financially weak individuals. It is the dentist to decide what minimum number of teeth should be restored to have the proper oral function. The aim was to find out the opinion of prosthodontists of Nepal regarding the suitability of shortened dental arch as treatment modality and how frequently is this treatment choice for an old aged Nepalese patient. Methods: A pretested close ended questionnaire was usedin this study.After taking ethical clearance from Nepal Health Research Council, online questionnaire was sent to the participants along with the consent. Analysis was done using SPSS (version 21) statistical software package. Descriptive statistics was used. Percentage and frequencies were calculated. Results: Among respondents, 96.2% (n=51) had heard about shortened dental arch therapy but 3.8 % (n=2) had never heard about it. Forty-two (79.2%) do support shortened dental arch. Eleven (20.8%) do not favorshortened dental arch. Their main reason for replacing molars was to improve masticatory function.Instead of shortened dental arch,n=5(45.5%) prefer cast partial denture and 6(54.5%) advice implant supported fixed prosthesis. Among Prosthodontists who recommended shortened dental arch therapy, eight (19.1%) always advised patients not to replace molars. Twenty-four (57.1%) prosthodontists who support shortened dental arch therapy mentioned chewing function in shortened dental arch patients as satisfactory. Conclusions: Majority of Prosthodontists agree that shortened dental arch is a suitable treatment option for older people in developing countries like Nepal. But the treatment is not employed in clinical practice as required.